SINERGITAS KOMPETENSI SOSIAL DOSEN TERHADAP PEMBENTUKAN SELF-DISCLOSURE MAHASISWA TINGKAT AWAL - Saaduddin; Nuzmi Sasferi (EDU RESEARCH, 2023)
Self-disclosure needs to be done by first year students because it is a way to adapt to a new environment. This study aims to determine the differences in self -disclosure based on gender and the relationship between lecturer's social competence and self-disclosure. The research sample was 146 first year students of FTIK IAIN Kerinci. The sampling technique used is cluster sampling. Data were collected using the Self Disclosure Scale which is an adaptation and modification of the Jourard Self-Disclosure Questionnaire and the Social Competency Scale which was compiled based on the aspects of the lecturer's social competence from Buss. The results of the analysis with the independent sample t-test resulted in t = -7.138. The contribution of lecturers' social competence to self -disclosure for male subjects is 19.5% while for female subjects it is 12.1%. The positive relationship between lecturer’s social competence and self-disclosure shows that the higher the lecturer's social competence, the higher the self-disclosure, and vice versa.